2013
DOI: 10.1038/srep02058
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of YF3:Eu3+ for improving photovoltaic performance of dye-sensitized solar cells

Abstract: In order to enhance the photovoltaic performance of dye-sensitized solar cell (DSSC), a novel design is demonstrated by introducing rare-earth compound europium ion doped yttrium fluoride (YF3:Eu3+) in TiO2 film in the DSSC. As a conversion luminescence medium, YF3:Eu3+ transfers ultraviolet light to visible light via down-conversion, and increases incident harvest and photocurrent of DSSC. As a p-type dopant, Eu3+ elevates the Fermi level of TiO2 film and thus heightens photovoltage of the DSSC. The conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…With regard to the second option, down-converting nanoparticles have been demonstrated to efficiently absorb UV light and re-emit visible light that can be harvested by the sensitizer in DSSCs 49,50 . Developing such routes to harvest all of the light of shorter wavelengths than 435 nm before it reaches the mesoporous TiO 2 , should allow for enhanced stability without the cost of decreased photocurrents 49,50 . With regard to removing the TiO 2 altogether, we have recently developed perovskite-based MSSCs, within which the mesoporous n-type TiO 2 is replaced with an insulating mesoporous Al 2 O 3 scaffold (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms3885mentioning
confidence: 99%
“…With regard to the second option, down-converting nanoparticles have been demonstrated to efficiently absorb UV light and re-emit visible light that can be harvested by the sensitizer in DSSCs 49,50 . Developing such routes to harvest all of the light of shorter wavelengths than 435 nm before it reaches the mesoporous TiO 2 , should allow for enhanced stability without the cost of decreased photocurrents 49,50 . With regard to removing the TiO 2 altogether, we have recently developed perovskite-based MSSCs, within which the mesoporous n-type TiO 2 is replaced with an insulating mesoporous Al 2 O 3 scaffold (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms3885mentioning
confidence: 99%
“…In another report by Wu et al [21] increase of 32 % photoconversion efficiency is found when compared with that of the DSSC without YF 3 :Eu 3? doping and correlated this increase due to the fact that dopant ions elevate the Fermi level of the TiO 2 film [21].…”
Section: Resultsmentioning
confidence: 82%
“…It is also reported that the 4f orbitals, in rare earth metal, increases the excited electron lifetime and slows down the recombination effect [22,28]. In another report by Wu et al [21] increase of 32 % photoconversion efficiency is found when compared with that of the DSSC without YF 3 :Eu 3? doping and correlated this increase due to the fact that dopant ions elevate the Fermi level of the TiO 2 film [21].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The high-energy photons are absorbed by the rare-earthdoped oxides and the energy is transferred to the sensitizers by spectrum conversion. Wu et al tried to make use of UV light by mixing a rare-earth-doped oxide (Eu 3Ć¾ -doped Y 2 O 3 ) colloid into the TiO 2 nanocrystalline film [11]. Gd 2 O 3 : Eu 3Ć¾ as a luminescence medium and p-type dopant was introduced into the DSSC by Xiao et al [12] Shen et al deposited NaGdF 4 :Eu nanocrystals on the front glass surface of as-prepared DSSC solar cell [13].…”
Section: Introductionmentioning
confidence: 99%